Antecedents and Consequences of Organizational Loyalty - Nassani, Abdelmohsen; Alqunaian, Wadha (The Arab Journal of Administration, 2024)
This study aimed to find out the antecedents and consequences of organizational loyalty, and to investigate the relationships between promotion opportunity, transformational leadership, loyalty, and retention among employees in the Kingdom of Saudi Arabia. Data was collected using a questionnaire which was distributed among a sample of 250 employees from various governmental and private sectors who were randomly selected to participate in the study. The results revealed significant relationships between the variables under investigation. Firstly, promotion opportunity was found to be positively correlated with transformational leadership, loyalty, and retention. Secondly, transformational leadership was positively correlated with both loyalty and retention. Finally, a positive relationship was found between loyalty and retention, indicating that higher levels of employee loyalty were associated with increased retention rates. These findings highlight the importance of promoting promotion opportunities within organizations, developing transformational leadership qualities among managers, and fostering a culture of loyalty to enhance employee satisfaction and reduce turnover.